Procurement And Distribution Of Integrated Values Study Of Gamers Characters - Annas, Mohammad; Humairoh, Humairoh (International Journal of Science, Technology & Management, 2024)
The aim of the study were to analyze the factors affecting gamers characters based on values in particular procurement, distribution and perception on how specific games must be developed. The procurement and distribution of both hardwares and its programmable various games becoming the essential in this study. Various values which formed the integrated values plus two other independent variables such as character identification and satisfaction rate were affecting the dependent variable, the intention of purchasing particular games. Structural equation analysis was done to justify if the dependent variables significantly affected by integration value, character identification and satisfaction rate. The result showed that Integrated Value of Purchading Game Items had a positive influence on Game Items Purchase Intention where the results of data processing showed that the standard coeficient was positive and the P Value showed a value of 0.000 which was in accordance with the requirement that the P Value must be below 0.05.